(untitled) (Research, Society and Development, 2022)
Bees represent the most important group of insects responsible for pollination. In recent years, the decline of these agents has been drawing attention, since bees are indispensable in the formation of many foods. In this context, the present study is the result of a quantitative and qualitative research, carried out in some supermarkets in the municipality of Serra/ES, aiming to verify the level of knowledge that consumers of these establishments have about the importance of bees, as well as the perception of the same about the importance of the action of these insects for the ecosystems. It is also sought to expose consumers to the vast amount of products present in their daily lives that often need directly from the work that is performed by bees. Thus, it was found that most people believe that bees develop important activities, however, respondents showed no interest in these insects. It was visible the lack of information on the subject and how much environmental education is necessary for the process of awareness / awareness of the community present in non-formal teaching spaces and in guaranteeing the preservation of these agents.